Importance of multiplanar reformation angiographic images for the detection of carotid web: A case series - Laura Zelada-Ríos; Danny Barrientos-Imán; Lourdes Simbrón-Ribbeck; Carlos Abanto Argomedo; Jorge Ramírez-Quiñones; Pilar Calle La Rosa; Ana Valencia Chávez; Ricardo Otiniano-Sifuentes (Brain Circulation, 2023)
Carotid web (CW) is considered a variant of intimal fibromuscular dysplasia. CW represents between 9.4% and 37% of ischemic strokes that were initially misclassified as “cryptogenic.” However, in Latin America, there is a lack of detection. We present 5 cases of ischemic stroke due to CW and discuss the usefulness of multiplanar reformatting (MPR) imaging in computed tomography angiography. The identification of CW with the use of tridimensional (3D) reconstructions and maximum intensity projection was 20%, the rest was misdiagnosed as atherosclerotic plaque. With the MPR, the identification of typical CW findings was improved, such as a thin septum, a shelf-like image, and a mountain shadow-like image. However, one must be alert to changes in the 3D disposition of the carotid bifurcation, as they may mask the typical CW findings. A good practice is to align the internal carotid artery exactly posterior to the external carotid artery in the sagittal plane.